Sex differences in shigellosis incidence rates: analysis of national data from nine countries using meta-analytic method. (14th June 2020) - Peer, Victoria; Schwartz, Naama; Green, Manfred S
Abstract: Background: Sex differences in the incidence of infectious diseases can provide insight to the biological mechanism of infection, disease susceptibility, severity and vaccine development. The consistency of age-specific sex differences in the incidence rates (IRs) of shigellosis is unclear. Methods: National data on cases of shigellosis by sex, age group and calendar year were obtained from nine countries, for a period of 6–25 years. The male to female incidence rate ratios (RR) were calculated by country, years and age group. For each age group, meta-analytic methods were used for computing pooled incidence RRs by country and years. Meta-regression was performed to estimate the contribution of age, country and time period to the differences in the male : female RRs. Results: In the age groups <1, 1–4, 5–9 and 10–14, there were excess IRs in males. The pooled incidence RRs (with 95% CI) were 1.21 (1.14–1.28), 1.17 (1.12–1.22), 1.04 (1.00–1.09) and 1.09 (1.01–1.18), respectively. In young adults, there was excess IR in females with RR = 0.80 (0.72–0.9). In middle aged and older adults, there was a slight excess in males with RR = 1.01 (0.89–1.15) and RR = 1.18 (1.09–1.28), respectively. In the meta-regression, age was the only variable that significantly contributed to the variation in the RRs. Conclusions: The higher IRs in male infants and young children does not appear to be related to behavioral factors and genetic and hormonal factors could be important. In the older age groups, the higher rates in adult females may be due to behavioral factors.